Taxonomic revision of Stinochiinae, Tenebrioninae and Diaperinae (Coleoptera: Tenebrionidae) from Malaysia - Hwayyiz, Darya Kareem (2017)
This study established the current taxonomic status of 30 species of darkling beetles (Coleoptera: Tenebrionidae) in Malaysia. A total of 392 specimens were examined. Thirty species has been identified belonging to three subfamilies, nine tribes and 17 genera with four potential new species and one potential new genus. A total number of 16 species were recorded for the first time in Malaysia namely Amarygmus metallicus, A. ovoides, Derosphaerus aeruginosus, Gonocephalum hispidocostatum, Leprocaulus rotundicollis, Promethis semisulcata, P. coracina, P. punctulator, P. opaca, Pseudonautes vagevittatus, Pseudoblaps javana, Strongylium erythrocephalum, S. orientale, S. various, Uloma sextuberosa and U. excise. A total of 42 internal and external morphological characteristic have been described for each species. Eleven structures for each species were illustrated based on their specific state namely antenna, labrum, labium, mandible, maxilla, pronotum, fore-leg, mid-leg, hind-leg, elytra, aedeagus. Taxonomic key to genera of subfamily Stinochiinae, genera of subfamily Tenebrioninae and the species of the genera Promethis, Strongylium, Eucyrtus, Gauromaia, Amargymus, Uloma, Tribolium species has been successfully developed. The distribution of Tenebrionidae species in Malaysia were shown in the maps for each species. The most common species is Tribolium castanum, Tribolium confusum, some species of the genus Promethis, the less common species is Uloma excisa, and rare species is Strongylium varians. A comprehensive checklist of Malaysian Tenebrionidae was developed for the first time with the total number of 207 species belonging to 64 genera. The highest number of the species has been found in Borneo followed by Penang and Malacca. The less number of the species have been found in Perak. The taxonomical effort produced from this study will be helpful for enhancing the species discovery while maintaining species inventories of Malaysian Tenebrionidae.